2017
DOI: 10.1186/s12879-017-2356-2
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Bordetella pertussis antibodies in adults in Hungary: results of an epidemiological cross-sectional study

Abstract: BackgroundPertussis (whooping cough) is well known to be underreported, particularly among adults, who can act as an infectious reservoir, potentially putting susceptible newborns at risk of serious illness. The purpose of this study was to estimate the seroprevalence of pertussis in adults in Hungary.MethodsThis epidemiological, cross-sectional study was conducted in adults in five general practitioners’ practices in Hungary. Serum anti-pertussis toxin immunoglobulin G (anti-PT IgG) antibody levels were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
4
10
0
1
Order By: Relevance
“…We also demonstrated that female sex significantly correlated with lower pertussis immunity and lower than median pertussis titers. This finding agrees with a study that found a correlation between reduced seropositivity for pertussis toxin and female sex in Hungary [45]. Sex differences in vaccine response occur for a variety of antigens although no clear pattern has been identified [46, 47].…”
Section: Discussionsupporting
confidence: 90%
“…We also demonstrated that female sex significantly correlated with lower pertussis immunity and lower than median pertussis titers. This finding agrees with a study that found a correlation between reduced seropositivity for pertussis toxin and female sex in Hungary [45]. Sex differences in vaccine response occur for a variety of antigens although no clear pattern has been identified [46, 47].…”
Section: Discussionsupporting
confidence: 90%
“…The determination of age associated antibody levels against B. pertussis is important in deciding the target age group for booster vaccination as well as for the study of disease epidemiology [15]. Our results suggest that a recent pertussis infection or reinfection after waning immunity exists among young or future parents, as well as among other elderly family members, similar to other authors' findings [7,15,17,18]. In our research, we found that anti-PT IgG levels ≥ 125 IU/mL were registered among three subjects (two men and one woman) aged over 60 years.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings recognized adults as the reservoirs of infection for pertussis for transmission to vulnerable infants, the new vaccination strategies in adults, such as the "cocooning strategy" and maternal immunization during the last trimester of pregnancy, or universal immunization may be considered [18,26,27,28].…”
Section: Discussionmentioning
confidence: 79%
“…12 Adolescents and adults are identified as the primary source of infection for newborns and young infants. 13 It is, therefore, of great importance to prevent and early detect pertussis among those populations. 4 The waning of immunity following pertussis vaccination and lack of administration of booster doses in addition to challenges related to the diagnosis can contribute to the persistence of pertussis.…”
Section: Introductionmentioning
confidence: 99%